Deconstructing theory of mind in schizophrenia - Stratta, Paolo; Bustini, Massimiliano; Daneluzzo, Enrico; Riccardi, Ilaria; D'Arcangelo, Melania; Rossi, Alessandro (Psychiatry research, 2011)
First- and second-order theory of mind (ToM) abilities seem to form a hierarchy of mind states within the same construct. If so, no ability in higher comprehension of intentionality would be possible when the previous one is failing. The purpose of the study is to investigate this hierarchy in a sample of schizophrenic subjects. Insofar as ToM defines processes involved in a multi-level social cognitive processing, they could be part of a scenario of specialized areas performing different parallel computations. Therefore, we further investigated the relationship of ToM scores to metacognitive indexes, widely demonstrated to be involved in social cognition, symptomatology and global functionality, in two independent samples of subjects with schizophrenia. Thirty-eight subjects with schizophrenia were preliminarily examined for first- and second-order ToM, using only one story in each order. Cross-tabulation of subjects according to their answers revealed that 13.2% of subjects gave incorrect answers to ToM I but correct answers to ToM II. A more extensive examination of first- and second-order ToM in a sample of 42 subjects with schizophrenia was then performed. The results confirmed the existence of a group of subjects (11.9%) scoring incorrectly at ToM I but correctly at ToM II, which is unexplainable if the hierarchical hypothesis were true. While both ToM scores were highly correlated with metacognitive scores on the Positive and Negative Syndrome Scale (PANSS), for both positive and negative clusters, and only second-order ToM was correlated with scores on the Global Assessment of Function (GAF). On the other hand, meta-cognitive indexes were correlated with both PANSS and GAF scores. First-order ToM was found to play an essential role in determining clinical severity. ToM I and II order scores share a minor part of variance. Instead of hierarchically ordered mind states, first- and second-order intentionality can represent different constructs. The ability to ‘understand others’, i.e. ToM, can be dissociable, suggesting the existence of an interconnected network of different constructs deputed to an adequate understanding and management of the social world complexity.